CLASSIFICATION AND SIGNIFICANCE OF RISKS IN GLOBAL COMPANIES: MODERN APPROACHES BASED ON COSO ERM AND ISO 31000 (American Journal of Business Management, Economics and Banking, 2026)
In the modern global economy, risk classification and management have become strategic priorities for multinational corporations. Rapid digital transformation, geopolitical instability, climate change, supply chain disruptions, and increasing regulatory requirements create a complex risk environment. This article examines the significance of risk classification in global companies and highlights modern approaches based on COSO ERM and ISO 31000 frameworks. Particular attention is given to strategic, operational, financial, technological, reputational, and ESG-risks. Effective risk classification enables companies to improve decision-making, allocate resources efficiently, strengthen internal control systems, and enhance long-term sustainability.